A dynamic gender-barriers framework to women's entrepreneurship: A competency-based perspective. Issue 1 (2nd January 2023) - Somià, Tatiana
ABSTRACT: This paper presents a new dynamic gender-barriers framework that aims to provide an updated, layered, and contextualized view of barriers and seeks to further a holistic understanding of women's entrepreneurship and its evolution. Barriers can be created, developed, or removed, in different areas and at different levels, changing over time. Gender barriers can overlap and cross different levels of analysis, and the removal or strengthening of a barrier can have a domino effect on other elements, generating unintended negative consequences, or creating synergies. This work focuses attention on individual barriers, related to a lack of specific competencies, and offers recommendations to practitioners, policy makers, and ecosystem supporters on how to effectively contribute to the competency development of women entrepreneurs. Strategies and policies to develop the competencies, through experiential entrepreneurship programs and executive coaching initiatives, can produce a ripple effect across different layers of society, contributing to reduce the gender gap.